(y-3)6y=4.5

Simple and best practice solution for (y-3)6y=4.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-3)6y=4.5 equation:



(y-3)6y=4.5
We move all terms to the left:
(y-3)6y-(4.5)=0
We add all the numbers together, and all the variables
(y-3)6y-4.5=0
We multiply parentheses
6y^2-18y-4.5=0
a = 6; b = -18; c = -4.5;
Δ = b2-4ac
Δ = -182-4·6·(-4.5)
Δ = 432
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{432}=\sqrt{144*3}=\sqrt{144}*\sqrt{3}=12\sqrt{3}$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-18)-12\sqrt{3}}{2*6}=\frac{18-12\sqrt{3}}{12} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-18)+12\sqrt{3}}{2*6}=\frac{18+12\sqrt{3}}{12} $

See similar equations:

| -7=-13+x | | 0.67b+5=20−b | | 3​x​+12+9​x​=72 | | 1.2vv=1.2 | | 4y^+20y+25+y^2=25 | | 75+15=10-10y | | -5u+8=-6u+18 | | 0.4x+x=210 | | 15-x=6+2x-6x | | f(-3)=7-3 | | 2w+7=2w-7 | | 2y+3(y+2)=16 | | 4y+y-5=10 | | x/6=3.5* | | 20+y=200 | | -104=4x-4(2x+16) | | -4u+2=-3u+6 | | 3y2-5=0 | | -10+n/4=9 | | 5(x+9)+8=9x-4(x-6) | | 3/4(f+8)=10 | | 5t2-12=0 | | 2x+13=4x | | 4u+2=3u+6 | | 6c+5cc=7 | | t=7.5+4 | | -36/(2x-1)^2=-36/361 | | 3/2(x-6)-(2x-4)=3/4 | | X3+3x-7=0 | | 42=4(m-3)+2(2m-3) | | 2x/10-5=x/5+1 | | 510+60m=75m |

Equations solver categories